1995
DOI: 10.1074/jbc.270.26.15707
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Phosphorylation and Dimerizing Domains of the α-Subunits of Na+/K+-ATPase

Abstract: Chemical cross-linking studies are among a number of experimental approaches that have suggested the functional significance of higher association states of alpha,beta-protomers of Na+/K(+)-ATPase. Formation of the phosphointermediate of the enzyme on Asp369 of the alpha-subunit is known to induce oxidative cross-linking of the alpha-subunits catalyzed by Cu(2+)-phenanthroline. To localize the phosphorylation-induced alpha,alpha-interface, we cleaved alpha at Arg438-Ala439 by controlled proteolysis and exposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 27 publications
1
27
0
Order By: Relevance
“…This loop contains the phosphorylation and nucleotide binding domains (28) for which significant structural information is provided by crystal structures of sarco(endo)plasmic reticulum calcium ATPase and EM structures of the Na,K-ATPase (29 -31). Furthermore, cross-linking experiments (16) and chimera studies (9,20) using the intact protein suggest that regions of association between oligomers occur in the M4M5 loop. We investigated the potential oligomerization of the Na,K-ATPase wild-type ␣␤ heterodimer with a mutant of the ␣-subunit lacking a significant portion of the M4M5 loop.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This loop contains the phosphorylation and nucleotide binding domains (28) for which significant structural information is provided by crystal structures of sarco(endo)plasmic reticulum calcium ATPase and EM structures of the Na,K-ATPase (29 -31). Furthermore, cross-linking experiments (16) and chimera studies (9,20) using the intact protein suggest that regions of association between oligomers occur in the M4M5 loop. We investigated the potential oligomerization of the Na,K-ATPase wild-type ␣␤ heterodimer with a mutant of the ␣-subunit lacking a significant portion of the M4M5 loop.…”
Section: Resultsmentioning
confidence: 99%
“…7 and 8. Briefly, physical interactions between ␣␤, ␣␣, and ␤␤ have been implicated from cross-linking studies (14,16,24,(37)(38)(39), co-immunoprecipitations have demonstrated the interaction of different ␣-subunit isoforms (19), thermal inactivation studies suggest ␣␣ contact (18), fluorescence resonance energy transfer provides distance measurements consistent with (␣␤) 2 (40), and low angle laser light scattering photometry coupled with high performance gel chromatography (41) as well as single molecule detection (17) indicate the presence of ␣␤, (␣␤) 2 , and higher order oligomers. Numerous studies in which half-site phosphorylation and halfor quarter-site ATP-analog binding stoichiometries have been interpreted in a model that proposes that the Na,K-ATPase co-exits simultaneously in the E1ATP, E2ATP, or EPATP forms (42).…”
Section: Resultsmentioning
confidence: 99%
“…This was initially proposed as a result of cross-linking experiments (41)(42)(43), but is supported with many other kinds of evidence as well: by saturation transfer EPR (44) and fluorescence energy transfer between subunits (45, 46), gel filtration (47), co-precipitation (48), kinetic evidence that could be best explained by the interaction of active sites (49), by measurements of the binding of different nucleotide analogs that suggest the existence of as many as four nonidentical sites (50), and by electron microscopy of solubilized particles (50). With electron microscopy of two-dimensional membrane crystals, Na,K-ATPase units (␣␤) have been observed in both monomeric and dimeric associations (51,52).…”
Section: Figmentioning
confidence: 99%
“…In previous studies we have also shown the regulation of the phosphorylation site by C-terminal domains of c~ [7,8], interactions between the N-terminal and C-terminal intramembrane helices of the co-chain [9], contact between the same helices of the ~-subunit and the single intramembrane helix of 13-subunit [9], and interactions between phosphorylation and dimerizing domains of c~-subunit [8]. Together, these findings clearly indicate that a multitude of intrasubunit and intersubunit domain~lomain interactions regulate the functions of the oligomeric Na+,K+-ATPase.…”
Section: Discussionmentioning
confidence: 99%
“…This controversy which has been reviewed repeatedly [3 5] is caused by disagreements on the extent of contaminants in the commonly used purified preparations of this membrane-bound enzyme and on the relative merits of different methods of protein assay used for the quantitation of enzyme subunits in these preparations. In the course of our recent structure-function studies on Na+,K+-ATPase preparations that are subjected to controlled proteolysis [6][7][8][9], it became evident that determination of relative phosphorylation capacities of the native enzyme and the enzyme whose cc-subunit is cleaved at Leu 266 Ala 267 may resolve the above controversy. Here, we present the results of such determinations, showing that, while this cleavage inhibits enzyme activity, it restores phosphorylation capacity to half of the phosphorylation sites that are dormant in the native enzyme.…”
Section: Introductionmentioning
confidence: 99%